Mechanistic investigation on moisture‐induced softening of poly(vinyl acetate)‐stiffened polyester fabrics. Issue 43 (15th April 2020) - Li, Yongxiang; Chen, Dongzhi; Cheng, Xiaoxia; Gao, Feng; Yang, Xiaobo; Mi, Yifang; Zhou, Qiubao; Lan, Shuxian; Cao, Zhihai
Abstract: Softening phenomenon of fabrics stiffened with eco‐friendly polymeric stiffening agents often occurs in service conditions, leading to a deteriorated stiffening style. It is highly desired to find the key factors that induce the softening of stiffened fabrics and to understand the softening mechanism. In this work, polyester fabrics and poly(vinyl acetate) (PVAc)‐based stiffening agent were chosen as the typical fabrics and polymeric stiffening agent, respectively. The stiffness value, a sensitive style index for the stiffening effect of fabrics, was selected to evaluate the variation of fabric stiffening effect during storage. A phenomenon of rapid softening was observed in the fabrics stiffened with various amounts of PVAc‐based stiffening agent. The stiffness value of stiffened fabrics decreased with the increase of hygroscopic amount. According to the hygroscopic kinetic data, the moisture‐induced plasticization effect of stiffening agent film, and the detachment of stiffening agent film from the fibers caused by the moisture‐induced weakening of interfacial interaction between the film and fiber, a possible softening mechanism of polymer‐stiffened fabrics was proposed. The hygroscopic‐drying cyclic experiments showed that the softening of stiffened fabrics was induced by the reversible plasticization effect and the irreversible interfacial damage between the film and fiber. Abstract :